The contribution of issues of “special educators” in undermining inclusive education in rural Kenya. - Omoke, Charles (IJRDO- Journal of Educational Research, 2020)
This paper is drawn from a study that investigated the perceptions of educators, parents and teachers in three rural districts in Kenya where national policy supports inclusive education consistent with the United Nations Convention on the Rights of the Child. A multiple case study design within a qualitative approach was used. Interviews and focus group discussions were used to collect data from three purposively selected case study schools. 42 participants were interviewed: 24 parents, 3 SEN teachers, 6 regular teachers, 3 head teachers, 3 district quality assurance and standards officers, as well as 3 focus group discussions, 3 observations and documentary analysis. The major finding of the study was that the education of children with SEN required ‘experts’ and ‘special’ resources unavailable in regular schooling leading to their exclusion. There is need to persuade parents and teachers that children with SEN can benefit from regular schooling.